The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.24869/psyd.2017.407
|View full text |Cite
|
Sign up to set email alerts
|

A SYSTEMATIC REVIEW OF TUMOR NECROSIS FACTOR-α IN POST-TRAUMATIC STRESS DISORDER: EVIDENCE FROM HUMAN AND ANIMAL STUDIES

Abstract: SUMMARY Background: Growing evidence suggests a pathophysiological role of cytokines in post-traumatic stress disorder (PTSD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…It is important to note, however, that altered blood cytokine levels as discussed here are not specific for affective disorders, but have also been found elevated in post-traumatic stress disorders (PTSD) (58, 59), obsessive-compulsive disorders (OCD) (60) or eating disorders (61). Additionally, low grade inflammation and cytokine elevation play a role in a number of physical diseases for example metabolic diseases such as diabetes and obesity as hallmarks of the metabolic syndrome.…”
Section: Innate Immune Response In Depressionmentioning
confidence: 88%
“…It is important to note, however, that altered blood cytokine levels as discussed here are not specific for affective disorders, but have also been found elevated in post-traumatic stress disorders (PTSD) (58, 59), obsessive-compulsive disorders (OCD) (60) or eating disorders (61). Additionally, low grade inflammation and cytokine elevation play a role in a number of physical diseases for example metabolic diseases such as diabetes and obesity as hallmarks of the metabolic syndrome.…”
Section: Innate Immune Response In Depressionmentioning
confidence: 88%
“…Cytokine TNF-α is regarded as a key inflammatory cytokine of the immune response, 26 but elevated levels of proinflammatory cytokines TNF-α and IL-1β have simultaneously been found in PTSD patients when compared to controls, 27 and it has been postulated that a combination of several elevated cytokines may be an indicator of PTSD. 26 We also found chemokine MCP-1 and cytokine IL-1β to increase over time in PTSD patients. It may be that increased TNF-α level accompanied by elevated IL-1β and MCP-1 could be viewed as biomarkers in PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, evidence has shown that cytokines play an important role in mental health and the pathophysiology of mental disorders, including disorders which are highly comorbid with EDs such as depression (Dowlati et al, 2010;Lichtblau et al, 2013), anxiety disorders (Baldwin et al, 2017;Quagliato and Nardi, 2017), post-traumatic stress disorder (Hussein et al, 2017;Waheed et al, 2018), and sleep disorders (Weschenfelder et al, 2012). Cytokines have also been linked with body weight and its regulation (Fonseka et al, 2016); for example, plasma levels of pro-inflammatory cytokine IL-6 have been shown to correlate positively with body mass index (BMI) (Himmerich et al, 2006;Schmidt et al, 2015).…”
Section: Introductionmentioning
confidence: 99%